Pengaruh etika dalam membangun kepatuhan wajib pajak orang pribadi - Aziz, Abdul (Maliki Interdisciplinary Journal, 2024)
Taxes are the main source of revenue in a country. Particularly in Indonesia, more than 70% of its government spending comes from tax collection. However, the implementation of taxation still faces many challenges, especially in the level of awareness and compliance of taxpayers and some ethical violations in tax payments. This article discusses how the role of organizations and tax officers to provide ethical understanding and tax education to individual taxpayers. To improve tax compliance, comprehensive knowledge is needed as well as how to apply distributive and procedural justice, and effective tax education. Good compliance from individual taxpayers will support the development and welfare of society in a country, especially in Indonesia.